Biological Cargo: Exosomes and their Role in Cancer Progression and Metastasis - Tripathi, Siddhant; Sharma, Yashika; Kumar, Dileep (Current Topics in Medicinal Chemistry, 2025)
Cancer cells are among the many types of cells that release exosomes, which are nano-vesicles. Because of their many potential applications, exosomes have recently garnered much attention from cancer researchers. The bioactive substances that exosomes release as cargo have been the subject of several investigations. The substances in question may operate as biomarkers for diagnosis or affect apoptosis, the immune system, the development and spread of cancer, and other processes. Others have begun to look at exosomes in experimental therapeutic trials because they believe they may be useful in the treatment of cancer. This review started with a short description of exosome biogenesis and key features. Next, the potential of tumor-derived exosomes and oncosomes to influence the immune system throughout the development of cancer, as well as alter tumor microenvironments (TMEs) and pre-metastatic niche creation, was investigated. Finally, there was talk of exosomes' possible use in cancer treatment. Furthermore, there is emerging consensus about the potential application of exosomes to be biological reprogrammers of cancer cells, either as carriers of naturally occurring chemicals, including anticancer medications, or as carriers of anticancer vaccines for immunotherapy as well as boron neutron capture therapy (BNCT). We briefly review the key ideas and logic behind this intriguing therapy recommendation.
Keywords: Exosomal cancer evolution